2013
DOI: 10.1371/journal.pone.0068596
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reprogramming Inhibits Western Diet-Associated Obesity

Abstract: A recent epidemiological study showed that eating ‘fast food’ items such as potato chips increased likelihood of obesity, whereas eating yogurt prevented age-associated weight gain in humans. It was demonstrated previously in animal models of obesity that the immune system plays a critical role in this process. Here we examined human subjects and mouse models consuming Westernized ‘fast food’ diet, and found CD4+ T helper (Th)17-biased immunity and changes in microbial communities and abdominal fat with obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(154 citation statements)
references
References 66 publications
(88 reference statements)
10
144
0
Order By: Relevance
“…While the former are often bacteria with fermentative capacity, recent work suggests that mucosa-associated microbes are responsible for many of the physiological functions normally attributed to the entire population. These taxa, which include Lactobacillus, Bifidobacterium, and Bacteroides, have a wide variety of functions ascribed to them: for example, Lactobacillus reuteri can inhibit Western-diet-associated obesity (26), Bifidobacterium infantis-conditioned medium enhances intestinal epithelial cell barrier function (27), Bacteroides thetaiotaomicron is known to induce gene regulatory events in the upper GI tract (28), and Bacteroides fragilis has been shown to influence immune development and enhance barrier function (29). Studies from our research group and others have shown that lactobacilli stimulate epithelial ROS generation and activate motility and proliferation events.…”
Section: Discussionmentioning
confidence: 99%
“…While the former are often bacteria with fermentative capacity, recent work suggests that mucosa-associated microbes are responsible for many of the physiological functions normally attributed to the entire population. These taxa, which include Lactobacillus, Bifidobacterium, and Bacteroides, have a wide variety of functions ascribed to them: for example, Lactobacillus reuteri can inhibit Western-diet-associated obesity (26), Bifidobacterium infantis-conditioned medium enhances intestinal epithelial cell barrier function (27), Bacteroides thetaiotaomicron is known to induce gene regulatory events in the upper GI tract (28), and Bacteroides fragilis has been shown to influence immune development and enhance barrier function (29). Studies from our research group and others have shown that lactobacilli stimulate epithelial ROS generation and activate motility and proliferation events.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired regulatory capacity leads to uncontrolled immune inflammatory responses, obesity and cancer later in life (2, 3). Our recent studies in mice have shown that Westernized diet (NWD)-associated obesity and cancer coincide with changes in gastrointestinal (GI) tract microbial communities and immune regulatory capacity preventable by dietary enrichment with beneficial bacteria(47). We test here whether these postulated effects of gut microbes transcend generations.…”
Section: Introductionmentioning
confidence: 99%
“…Through biopsies in the duodenal mucosa of healthy adults receiving either live or heat-killed L. plantarum , Baarlen et al [15] demonstrated a regulation of the key inflammatory transcription factor in subjects receiving live bacteria. Supporting this immunomodulatory role of Lactobacillus , Poutahidis et al [16] showed that Lactobacillus reuteri administered in the drinking water facilitated resistance to diet-induced obesity, despite L. reuteri failing to colonize the intestinal cavity. Subsequent experiments confirmed that L. reuteri induced an adipose-specific increase of anti-inflammatory regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%